Controlled trial of three weeks nicotine replacement treatment in hospital patients also given advice and support. Issue 8 (1st August 2002) - Hand, S; Edwards, S; Campbell, I A; Cannings, R
Abstract : Background: Smoking is a major public health issue, estimated as causing 120 000 deaths in the UK per year. Smoking cessation is an important aspect of the treatment of many diseases. Nicotine replacement therapy (NRT) has been shown to increase cessation rates among healthy volunteers and in general practice, but it is not clear whether it has an effect in hospital patients. Methods: Patients referred by their hospital doctor to the smoking cessation counsellor and who agreed to participate in the study were randomised to receive either NRT given as a nicotine patch daily and a nicotine inhalator on an as needed basis plus advice and support (AS+NRT), or to receive just advice and support (AS). Claims of smoking cessation were validated at 1 week, 3 months, 6 months, and 1 year by carbon monoxide (CO) breath testing. Results: A total of 245 patients were randomised, 136 AS+NRT and 109 AS. There were no significant demographic differences between the two groups at baseline. At 1 year 35 (14%) had sustained cessation confirmed by a CO breath test, 20/136 (15%) AS+NRT and 15/109 (14%) AS, p=0.857. One hundred and ten patients gave up smoking for at least 1 week, 54% AS+NRT and 33% AS (p<0.001). By 6 months there was no significant difference between the two groups (22/136 (16%) AS+NRT and 15/109 (14%) AS). Conclusion: In hospital patients NRT, given as regular daily patches plus an inhalator to be used as needed, did not add to the smoking cessation rate achieved at 1 year by regular advice and support, despite significantly increasing the cessation rate at 1 week.